PENGEMBANGAN CD INTERAKTIF BERBASIS PROGRAM ADOBE FLASH CS6 UNTUK PEMBELAJARAN GEOGRAFI MATERI POKOK HUBUNGAN MANUSIA DAN LINGKUNGAN AKIBAT DINAMIKA HIDROSFER SISWA KELAS X DI SMA NEGERI 2 BATANG (Edu Geography, 2016)
The study goal was to determine the proper media and analyze student learning outcomes with Adobe Flash CS6 media. Method of research is the development of R & D. Stages of R & D include the potential and problems, data collection, product design, validation, revision, small-scale trials, product revision, implementation of large scale. Variable research is the validation of media experts and materials, student activities, learning outcomes, and the positive response of students. Data collection techniques including observation, questionnaires, documentation, and testing. The results showed that the learning media feasible with student activities and student responses were good. Learning outcomes are increased in the amount of 16.5% with an average value of 44.75 before using the media and after using the media 78 625. The conclusions of this research is learning media Adobe Flash CS6 as feasible and can improve student learning outcomes in class X hydrosphere material with suggestions for teachers to create interactive learning media for active students.